2018
DOI: 10.1074/jbc.tm118.000372
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination and the repair of DNA double-strand breaks

Abstract: Homologous recombination enables the cell to access and copy intact DNA sequence information in , particularly to repair DNA damage affecting both strands of the double helix. Here, we discuss the DNA transactions and enzymatic activities required for this elegantly orchestrated process in the context of the repair of DNA double-strand breaks in somatic cells. This includes homology search, DNA strand invasion, repair DNA synthesis, and restoration of intact chromosomes. Aspects of DNA topology affecting indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
450
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(480 citation statements)
references
References 113 publications
(136 reference statements)
3
450
0
1
Order By: Relevance
“…DNA recombination triggered by tandem paired nicking results in consequences analogous to those described in Holliday's model (Holliday, 1964;Liu and West, 2004). It is now widely accepted that DSBs promote homologous recombination (HR) (Chapman et al, 2012;Wright et al, 2018). Meanwhile, our study demonstrated that iso-positional nicking of two homologous DNA fragments promotes a type of recombination that is similar to HR.…”
Section: Discussionsupporting
confidence: 58%
“…DNA recombination triggered by tandem paired nicking results in consequences analogous to those described in Holliday's model (Holliday, 1964;Liu and West, 2004). It is now widely accepted that DSBs promote homologous recombination (HR) (Chapman et al, 2012;Wright et al, 2018). Meanwhile, our study demonstrated that iso-positional nicking of two homologous DNA fragments promotes a type of recombination that is similar to HR.…”
Section: Discussionsupporting
confidence: 58%
“…The 3ā€²ssDNA formed is first coated by RPA and then by the Rad51 recombinase forming a filament that will engage the search for a homologous sequence. This search, if successful, will be followed by the strand invasion of the template sequence, DNA polymerization and resolution of the D-loop structure to restore intact duplex DNA (Symington et al 2014;Wright et al 2018).…”
Section: Resection a Ticking Clock For Homology Search?mentioning
confidence: 99%
“…RPA, in turn, recruits proteins of the Rad52 epistasis group, such as Rad51, and these carry out strand invasion of the homologous template (Shinohara et al 1992;Sung 1994;Baumann et al 1996;Fortin and Symington 2002). New DNA synthesis copying the invaded duplex seals the DSB and after the resolution of the recombination intermediate structures, two intact DNA duplexes are restored (Symington et al 2014;Wright et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MCM8-9 have been implicated in HR steps downstream of RAD51 loading 12,19 , including DNA damage-induced DNA synthesis at acutely stalled replication forks, presumably the sites of one-ended DSBs, and at I-SceIgenerated two-ended DSBs 19 . These observations raise the possibility that MCM8-9 can facilitate D-loop extension during recombination-associated DNA synthesis 19,20 .…”
Section: Main Textmentioning
confidence: 97%